Leadership Style, Intellectual Capital, Corporate Social Responsibility and Corporate Performance: A Comparative study between two Indonesian Industries - Rilla Gantino; Endang Ruswanti; Taufiqur Rahman (Journal of Accounting Research, Organization and Economics, 2019)
Objective – The purpose of this paper is to examine the effect of of leadership style, intellectual capital and corporate social responsibility on performanceDesign/methodology – Data was gathered from two sources. To assess the leadership style, questionnaires were distributed and filled by staff working in sample companies from both. Meanwhile, secondary data collected from financial statements from 2012 to 2018 of each company samples. This study uses census sampling method.Results – The results of this study demonstrated that leadership style has a negative influence on ROA, ROE and Sales Growth for both sector. The intellectual capital has a significant positive influence on ROA, ROE and Sales Growth. Furthermore, in the infrastructure, utilities, and transportation sector, the corporate social responsibility has a negative influence on ROA, a significant positive effect on ROE and not significant on sales growth. Meanwhile, the results from the companies in the basic industries and chemical sectors shows that corporate social responsibility has a negative influence on ROA, ROE and sales growth.Research limitations/implications – A study which compare companies from different industries is still limited. This study focuses on Basic Industry and Chemicals sector and the Infrastructure, Utilities and Transportation Sector in Indonesia, and it is possible that these results are only applicable to the these sector. More research is therefore needed to further understand the contribution of performance to other sectors.Practical Implication - The results are important for management policy development, for example, in terms of prescribing the competences of leadership to enhance firm performance